Análisis de la competencia de los medios de comunicación digitales de la ciudad de Babahoyo en el año 2022 - Bayas Peña, Karely Jacqueline (2023)
The analysis of competition among digital media outlets in the city of Babahoyo in 2022 reveals crucial insights into the local media landscape. The research identified that media outlets implementing innovative strategies and diversifying their content formats, including videos, infographics, and live broadcasts, experienced higher levels of audience interaction and retention. Additionally, media outlets focusing on relevant local topics and adopting innovative thematic approaches gained a more engaged and loyal audience. Furthermore, effective interaction with the audience through comments, surveys, and social media engagement played a crucial role in audience retention and participation. The theoretical application proposal focuses on the implementation of programs for effective journalistic storytelling and fostering audience interaction to transform passivity into activism. It is expected that this proposal will improve the quality of content produced by local digital media and increase their influence in information provision and audience engagement. Expected outcomes include a more active and participative audience, an increase in the number of visits to each news item, and a revitalization of digital media in Babahoyo.